Biology of Trichogramma cordubensis (Hym., Trichogrammatidae) under different photoperiods - Garcia, Patrícia (1997)
This work was carried out to study the effect of photoperiod on Trichogramma cordubensis Vargas & Cabello biology. T. cordubensis was reared on Ephestia kuehniella Zeller eggs at 20°C and 75±5% of HR. The essay comprised different photophase (L): scotophase (D) combinations thal simulated the day length of summer (16:8), winter (8: 16) and spring or autumn (12:12) seasons in the Azores. Photoperiod did not influence the parasitoid longevity, emergence rate and parasitism. However, it had a significant effect on the parasitoid egg to adult developmental time, the last enlarging with increasing photophase.